Cut-off values for normal sperm morphology and toxicology for automated analysis of rat sperm morphology and morphometry. (2nd January 2018) - van der Horst, G; Skosana, B; Legendre, A; Oyeyipo, P; du Plessis, SS
Abstract: We used automated sperm morphology analysis to investigate rat sperm morphometry and morphology in Sprague-Dawley and Wistar rats in three research centers to develop normal baseline values for sperm morphometry and to quantify the percentage of morphologically normal sperm in healthy rats. The participating centers were IRSN in Paris, France (Sprague-Dawley rats), University of the Western Cape, South Africa (Wistar rats) and Stellenbosch University (Wistar rats), South Africa. All three centers used identical sperm isolation techniques from the cauda epididymis, the same staining protocols, identical computer-aided sperm morphometry analysis (CASMA) software and microscopes with similar optics. With CASMA, fully automated analysis of the different parts of stained sperm, e.g., head, acrosome, mid-piece, can be performed, many sperm morphometric features can be measured accurately and eventually normal sperm morphology can be defined. We found that it is possible to distinguish sperm morphometric characteristics of Sprague-Dawley and Wistar rats. We also developed cut-off values for evaluating the percentage normal sperm in these two rat strains using the automatic analysis mode. Normal sperm morphology varied between 67 and 74% by contrast with previous findings of > 90%.